PENGARUH LAMA PEMAKAIAN ALAT KONTRASEPSI SUNTIK DMPA TERHADAP DISFUNGSI SEKSUAL DI WILAYAH KERJA PUSKESMAS KAMANDRE - Ny Patmahwati (Lembaga Penerbit dan Publikasi Ilmiah (LPPI) Universitas Muhammadiyah Palopo, 2018)
Injectable contraceptive Depot Medroxy progesterone Acetate (DMPA) is one of the hormonal contraceptives that is widespread and increases over time. According to WHO, today almost 380 million couples run family planning and 66 - 75 million of them, especially in developing countries, using hormonal contraceptives. The use of contraceptive DMPA injections for a long time will cause sexual dysfunction in the form of decreased libido. This research is a research to find out the influence of long time use of DMPA injection tool to decrease libido in working area of Kamandre Health Center. The data collection time approach in this study is cross sectional. Population in this research is all mother of KB acceptor, who visited at Kamandre Health Center of Luwu Regency at. The sample in this research is all of the DM acceptors of DMPA acceptor who visited at Kamandre Public Health Center during October - November 2017 with Sampling technique of Pourposive Sampling. The result of the study showed 38 respondents old use Kb injection <24 months 11% which decreased libido and 39% did not decrease libido. While the duration of use Kb injection> 24 months 47% decreased libido and 3% did not decrease libido, so that the result of computerized statistic test obtained p value is 0.000 (p <0,005) means Ho rejected and Ha received. From the results of the study can be concluded that there is Influence between the long use of DMPA Injecting with Sexual Dysfunction in the Working Area of Kamandre Puskesmas Luwu District. Keywords : Duration of DMPA Injection Usage, Decreased Libido